Application of multiple binding sites for LAMP primers across P. falciparum genome improves detection of the parasite from whole blood samples - Mgawe, Cavin; Shilluli, Clement; Nyanjom, Steven; Odari, Eddy; Linnes, Jacqueline C.; Kanoi, Bernard N.; Gitaka, Jesse; Ochola, Lucy (Frontiers in Malaria, 2023)
Introduction Malaria remains a significant health concern, particularly in regions with widespread prevalence. As the transmission rates decrease, there is a rise in low-density infections with the causative parasite, P. falciparum, that often escape detection through standard point-of-care diagnostic tools. In-low transmission areas, even few undetected cases can trigger outbreaks, necessitating rapid and sensitive diagnostics. Loop-mediated isothermal Amplification (LAMP) stands out as a nucleic acid technique that can easily utilizes un-processed samples such of saliva, urine, and lysed whole blood templates for a sensitive detection. However, most nucleic acid tests detect genes with few copies per parasite making it difficult to detect low-density parasitaemia. Methods We selected Pfr364 multi-copy repeats of the P. falciparum genome as a target for amplification due to their higher copy number, ideal for rapid amplification, addressing amplification drawbacks of limited parasites DNA. We used a sequence clustering approach to design a novel set of LAMP primers, capable of binding to multiple sites. Subsequently, we developed a hydroxynaphthol blue (HNB) colorimetric LAMP assay, using genomic DNA obtained from the 3D7 strain cultivated in vitro. This assay’s performance was validated using archived clinical samples of both whole blood and matched saliva, ensuring accuracy through comparative analysis against gold standard, nested PCR, targeting the 18S RNA gene. Results The HNB-LAMP assay achieved rapid amplification within 15 minutes and exhibited high sensitivity with a limit of detection of 1 parasite. Further, the LAMP assay was robust in whole blood lysed with Triton X-100 and heat-treated saliva clinical samples. Against nested PCR, the assay showed sensitivity of 100% for whole blood and 40% for saliva samples. Moreover, co-analysis with the nested PCR showed a perfect agreement between the two techniques. (K = 0.99 for whole blood, and 0.66 for saliva). Conclusion Our study presents a method for detecting P. falciparum using LAMP, which results in increased sensitivity, shorter assay times, and a simpler workflow than nucleic acid tests relying on conventional DNA extraction and additional equipment for result interpretation. These findings hold great promise for improved malaria diagnosis, especially in settings where low-density parasitaemia is prevalent and rapid and accurate malaria detection is crucial.